Potensi Akad Mudarabah dalam Kondisi Pandemi Covid-19 di Indonesia - Achmad Fageh (Universitas Islam Lamongan, 2020)
There are several government roles in making it a widespread development in the state of Indonesia. Starting from the existence of government agencies that participate and supervise and make rules as a way to sharia economy, to the role of Sharia banks that have been seen its role until in the early 2020 before the presence of Corona viruses that attacked Indonesia. It is evidence that scholars and governments also support the existence of the Mudarabah system in the Sharia economy in Indonesia. Bank Syari'ah Indonesis itself has been awarded as the biggest retail Islamic banking